IMPLEMENTASI KAMUS KATA BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN BAHASA ANAK DI PAUD KB DOA BANGSA, LAMPUNG TENGAH LAMPUNG TENGAH - Mela Anggraini (UNISAN JURNAL, 2025)
Language skills are a crucial aspect of early childhood development, supporting children's ability to think, interact, and learn. This study aims to examine the implementation of a picture word dictionary in enhancing children's language skills at PAUD KB Doa Bangsa, Lampung Tengah, Central Lampung. The method used is Classroom Action Research (CAR) with two cycles of action. Data were collected through observation, interviews, and documentation, and analyzed using a qualitative descriptive approach. The results show an improvement in children's language skills, particularly in vocabulary and the ability to construct simple sentences. The picture word dictionary proved to be effective in attracting children's interest and facilitating their understanding of new words. In conclusion, the systematic use of picture dictionaries can serve as an effective alternative for language learning in early childhood education (PAUD).